Size at birth and cognitive function among rural adolescents: a life course epidemiology study protocol of the Kisalaya cohort in Mysuru, South India - Piers Dawes; Anisa Khan; Kavitha Ravi; Karl Krupp; Murali Krishna; Smitha Malenahalli Chandrashekarappa; John Newall; Poornima Jaykrishna; Chaithra V Urs; Satyapal Puri Goswami; Anjali Arun (BMJ Publishing Group, 2020)
Introduction It is proven that adverse intrauterine environment results in 'early life programming,' alterations in metabolism and physiological development of the fetus, often termed as 'Developmental Origins of Health and Disease' (DOHaD) resulting in a smaller size at birth, greater non-communicable diseases (NCD) risk factors during childhood and adolescence, and cardiometabolic disorders in adulthood. Nevertheless, very few studies have examined the relationship between DOHaD programming and cognition. This study aims to examine if impaired prenatal growth indicated by birth weight is associated with cognition among adolescents in the Kisalaya cohort, a rural birth cohort in South India, thus providing newer insights into DOHaD programming for adolescent mental health in a low-income and middle-income country setting.Methods and analysis Kisalaya cohort was established in 2008, to provide integrated antenatal care and HIV testing using mobile clinics to improve maternal and child health outcomes. This cohort included pregnant women residing in 144 villages of Mysuru Taluk (rural) who received antenatal care through mobile clinics and delivered their children between 2008 and 2011. Data related to mother-infant dyads for all pregnant women who received care in the Kisalaya programme are available for this study. Presently, children born to women who received care through Kisalaya are adolescents between 10 and 12 years. At this point, information would be collected on sociodemographic data and assessments of mental health, stressful life events, cognition, vision, speech, language, hearing and anthropometric measures would be done and relevant maternal data and child data, available from the cohort would be retracted for analysis. We plan to retrace as many adolescents as possible out of 1544 adolescents who are currently available for study excluding twins, abortions, stillbirths and postdelivery deaths. Analyses will be extended to construct a life course pathway for cognition using structural equation modelling.